2013
DOI: 10.1371/journal.pone.0055126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Uptake of Chitooligosaccharides through Chitoporin from the Marine Bacterium Vibrio harveyi

Abstract: BackgroundChitin is the most abundant biopolymer in marine ecosystems. However, there is no accumulation of chitin in the ocean-floor sediments, since marine bacteria Vibrios are mainly responsible for a rapid turnover of chitin biomaterials. The catabolic pathway of chitin by Vibrios is a multi-step process that involves chitin attachment and degradation, followed by chitooligosaccharide uptake across the bacterial membranes, and catabolism of the transport products to fructose-6-phosphate, acetate and NH3.Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 52 publications
9
81
0
Order By: Relevance
“…To resolve the uncertainty surrounding the function of chitoporin, we previously performed liposome swelling assays to demonstrate possible translocation of chitohexaose, but not other non-chitooligosaccharides, through VhChiP (11). To quantify translocation, we employed the BLM reconstitution technique based on channel occlusion for ion current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve the uncertainty surrounding the function of chitoporin, we previously performed liposome swelling assays to demonstrate possible translocation of chitohexaose, but not other non-chitooligosaccharides, through VhChiP (11). To quantify translocation, we employed the BLM reconstitution technique based on channel occlusion for ion current.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific function of chitoporin as a sugar-specific channel had never been clearly elucidated. We recently employed black lipid membrane (BLM) 4 reconstitution and liposome swelling assays to demonstrate that chitoporin from V. harveyi (VhChiP) is a pore-forming channel that performs highly specific translocation of chitooligosaccharides (11). In the present study, we focused on the kinetic evaluation of single chitooligosaccharide translocation through a single VhChiP.…”
mentioning
confidence: 99%
“…In contrast to the parental strain, a mutant strain lacking VfChiP did not grow on GlcNAc 3 , implying that VfChiP was selective for chitooligosaccharides (6). We recently identified and characterized the chitin uptake channel (so-called VhChiP) from the bioluminescent marine bacterium Vibrio harveyi (7,8). VhChiP is a trimeric OmpC-like porin located in the outer membrane and responsible for the molecular uptake of chitin breakdown products that are generated by the action of secreted chitinases (4, 9 -11).…”
mentioning
confidence: 99%
“…We recently identified chitoporin from V. harveyi (known as VhChiP) as a pore-forming channel that performs highly specific translocation of chitooligosaccharides (9,10). Single channel recordings using a black lipid membrane (BLM) 4 reconstitution technique showed that VhChiP inserted into the artificial bilayer membranes and formed a trimeric channel that remained steadily open under applied potentials of up to Ϯ150 mV.…”
mentioning
confidence: 99%